Implementasi Metode WASPAS Untuk Menentukan Pengawas Vendor Terbaik Pada PT Sumber Mutiara Indah Perdana - Syahputra, Bayu; Sellyana, Ari; Desriyati, Welly (Sekolah Tinggi Teknologi Dumai, 2025)
PT Sumber Mutiara Indah Perdana is a factory that operates in the industrial sector, namely building a sugar factory located on Jl. Pelintung, Dumai, Riau. Every month the company always gets a project tender to collaborate with anothercompany, the company always gives opportunities to employees who are trusted to handle a project. However, the problem faced by the company is that many employees want to take over a project, because if an employee succeeds and wins the project, the employee will get a bonus, so the company is very confused about choosing who will be the vendor supervisor if they get a new project. The company only uses Excel or a performance evaluation form to assess the performance of employees who will be trusted to handle a project. So far, companies only assess the performance of employees who are close to managers, who always get good ratings, resulting in gaps between employees and becoming an obstacle for companies to be able to develop a company's business. For this reason, a computerized system is needed that can help companies minimize the emergence of jealousy between fellow employees in becoming supervisors of vendors on a project.